1991
DOI: 10.1136/oem.48.3.193
|View full text |Cite
|
Sign up to set email alerts
|

Presence of acute phase response in coal workers' pneumoconiosis.

Abstract: To evaluate the role of personal factors in pneumoconiosis, several acute phase proteins were studied in 62 coal miners without acute illnesses and classified as having no pneumoconiosis (n = 19), simple pneumoconiosis (n = 23), or complicated pneumoconiosis with pro-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 9 publications
1
4
0
Order By: Relevance
“…Unusually, a series of non-specific biomarkers such as CRP, AAT and LDH were assessed in our study on silicosis; we have not found any prior study in which ferritin has been analysed. However, several studies 33 , 34 show elevated CRP levels, a non-specific biomarker, in patients exposed to silica and increasing according to silicosis severity, as was the case in our study. Our series shows elevated levels of alpha-1-AT, in a similar fashion to Montes II et al 35 .…”
Section: Discussionsupporting
confidence: 76%
“…Unusually, a series of non-specific biomarkers such as CRP, AAT and LDH were assessed in our study on silicosis; we have not found any prior study in which ferritin has been analysed. However, several studies 33 , 34 show elevated CRP levels, a non-specific biomarker, in patients exposed to silica and increasing according to silicosis severity, as was the case in our study. Our series shows elevated levels of alpha-1-AT, in a similar fashion to Montes II et al 35 .…”
Section: Discussionsupporting
confidence: 76%
“…Accordingly, workers from Swedish iron foundries did not present changes in their circulating CRP blood levels 52 , and neither did patients with different stages of silicosis 28 . However, in other studies including workers exposed to silica, an increase in serum CRP was detected 45 , 53 , 54 . Our results for CRP could be explained as a consequence of the fact that the inflammatory state of the patients may have become chronic, rather than acute, due to the time elapsed between exposure to silica, diagnosis and sampling, although further research is needed to confirm this hypothesis.…”
Section: Discussionmentioning
confidence: 67%
“…Ambient air pollution particles effect several changes in the peripheral blood, including decreases in red cell number,71 elevations in white blood cell counts,71 and increases in C-reactive protein,71 fibrinogen,38,71,72 and blood viscosity;71,73 the last two potentially contribute to the association of ambient PM with thrombotic events 74. Other particles have comparable effects on hemorheologic indices 75,76…”
Section: Particle-related Lung Injurymentioning
confidence: 99%